The effect of geographical origin of perch (Perca fluviatilis L. 1758) populations on growth rates under natural and aquaculture conditions: a review. (November 2015) - Pimakhin, A.; Kouřil, J.; Stejskal, V.; Žák, J.
Summary: Wild Eurasian perch populations ( Perca fluviatilis L.) are characterized by annual fluctuations in abundance as a result of environmental and intra‐specific interactions. Variations in these interactions may be the source of differences in the characteristics of perch originating from different geographic regions. Perch abundances are higher in northern biotopes than in the south, although climate conditions in the latter would seem to be more conducive to perch growth. Research conducted on the growth of wild Eurasian perch strains from various regions of Europe reared in recirculating aquaculture systems (RAS) revealed differences among strains in body weight, survival, morphometric parameters, and other biological characteristics such as growth rate and feeding. Knowledge of survival and growth differences among perch strains is necessary as a tool for improvement of perch culture. Identification of the strain best adapted to RAS is the first step in a stock selection program.